2020
DOI: 10.1007/s10995-020-02969-5
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Florida’s Zika Response Using the WHO Health Systems Framework: Can We Apply These Lessons to COVID-19?

Abstract: Objectives From 2016 to 2018 Florida documented 1471 cases of Zika virus, 299 of which were pregnant women (Florida Department of Health, https ://www.flori dahea lth.gov/disea ses-and-condi tions /mosqu ito-borne disea ses/surve illan ce.html, 2019a). Florida's response required unprecedented rapid and continuous cross-sector communication, adaptation, and coordination. Zika tested public health systems in new ways, particularly for maternal child health populations. The systems are now being challenged again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…This finding was comparable with studies done in many countries showing how the complex interactions interfered with the outcomes [9][10][11]44,45]. In a study looking at Zika's outbreak management, it was found strong collaboration among stakeholders and efficient surveillance systems generating database of Zika-positive pregnant women shared effectively among healthcare providers were the main drivers for successful service deliveries [9]. In a nutshell, health systems relied on smooth and efficient interactions between the fundamental elements to deliver quality services while facing a crisis [47].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding was comparable with studies done in many countries showing how the complex interactions interfered with the outcomes [9][10][11]44,45]. In a study looking at Zika's outbreak management, it was found strong collaboration among stakeholders and efficient surveillance systems generating database of Zika-positive pregnant women shared effectively among healthcare providers were the main drivers for successful service deliveries [9]. In a nutshell, health systems relied on smooth and efficient interactions between the fundamental elements to deliver quality services while facing a crisis [47].…”
Section: Discussionsupporting
confidence: 90%
“…While the numbers of tests conducted were increasing throughout the outbreak, earlier identification, engagement and collaboration with universities and private sectors were the areas reported requiring improvements for the country to better cope with the surge of cases. This finding was comparable with studies done in many countries showing how the complex interactions interfered with the outcomes [9][10][11]44,45]. In a study looking at Zika's outbreak management, it was found strong collaboration among stakeholders and efficient surveillance systems generating database of Zika-positive pregnant women shared effectively among healthcare providers were the main drivers for successful service deliveries [9].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is a public health priority to develop sustainable models of healthcare by strengthening local health systems, especially with the introduction of the six building block framework of health systems by the World Health Organisation 53–55 . While these blocks are not suitable to capture the dynamics and interplay between complex system elements, 56 it provided directions to decide on the programme aspects for realist evaluation of the REACH programme 55,57 …”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, the author indicates that AARs are essential to improving public health emergency preparedness by contributing to the essential evidence-based feedback loop and sustained application within public health practice. A separate study from Marshall et al, 25 examining Florida's response to the 2016-2018 Zika Virus outbreak and assessed collaboration and adaptation across systems of care to provide recommendations for response to future outbreaks, including potential implications for COVID-19. While this study did not conduct an AAR, the WHO Health Systems Framework was used to systematically assess the PHEM response, and utilized journeymapping and stakeholder engagement techniques to collect data for their evaluation which highlighted several areas of improvement in these indicator areas.…”
Section: Learning From Past Emergenciesmentioning
confidence: 99%